Keluar Jalur Manajerial - Haryanto F Rosyid (Jurnal Psikologi, 2012)
The aim of this research is to figure out, number of employee included in high potential employees among civil servants in Jogjakarta Special District, and percentage of those categorized in high potentials, who underwent managerial derailment. Besides, this research wanted to identify causes of managerial derailment. Jogjakarta is an specific government area consists of one municipality led by a mayor, and 4 regencies, each led by a regent. Data of high potential employees in documentary owned by the head of Regional Employment Body in Jogjakarta Government area. The sum of four heads, and a secretary of Regional Employement Body, were interviewed to reveal the information. The result of this study showed only 5.91% of the high potential employees underwent managerial derailment, far below another research study, indicated the number of 25%. There are two factors influencing managerial derailment, first, internal factor, and second external factor of the employee. Keywords: derailment, high potential, managerial derailment